Relokasi Gempa Low Frequency pada Gunungapi Papandayan menggunakan Optimasi Very Fast Simulated Anneling: Muhammad Mifta Hasan, Hetty Triastuty, Bagus Jaya Santosa, Amien widodo - Muhammad Mifta Hasan, Muhammad Mifta Hasan; Hetty Triastuty, Hetty Triastuty; Bagus Jaya Santosa, Bagus Jaya Santosa; Amien Widodo, Amien Widodo (Jurnal Fisika dan Aplikasinya, 2025)
Papandayan which is stratovolcano mountain has high seismic activity especially low frequency event that associate with hydrothermal activity. Calculation of hypocenter used VFSA optimization with basis of random process. Searching of model parameters following Cauchy probability distribution has found the best fit model parameters rapidly. Location of low frequency event at Papandayan volcano concentrate beneath Mas crater and Nangklak crater with around 0.56 km depth and maximum misfit reach 6.4297.